Liburnian Imitations of Astragal Belts (Archaeologia Adriatica, 2008)
In several graves at the hillfort of Dragišić near Šibenik (Dalmatia, Croatia) large numbers of multiheaded pins of the Iapodian-Liburnian type of astragaloid form were found. The article discusses the idea that the heads of the pins were actually in a secondary function, and that these were local Liburnian imitations of astragal belts. Multiheaded pins come in two types, and to manufacture the astragal belts, the heads were utilized of multiheaded pins of type A, those that have four astragaloid profiles. Eight examples were found in grave 5 at Dragišić and according to the supposition of Z. Brusić, the director of the excavations, they were attached to a leather belt. Multiheaded pins are a mutual component of the Istrian, Iapodian, and Liburnian Iron Ages groups and are dated from the 8th century BC and onwards, while most have been found at Iapodian sites.Astragal belts appear at the end of the 6th century BC in the central Balkan- Illyrian region, and via cultural and trade connections were adopted by the pre-Celtic and later Celtic populations in the Danube basin, and particularly in Srijem/Sirmia. Finds of the Sirmian type of late Hallstatt belt are most numerous, and the type is dated to the 5th century BC. It is composed of separate joints with four astragal elements and has a rectangular platelet with three loops for fastening. The Osijek type is the oldest type of Celtic astragal belt, dated to the Beograd 2 phase = LT C, while the other types are late La Tène. They are attribute to the Celtic Scordisci and are part of female attire.The inspiration for putting together a belt with the aid of astragaloid pin heads arrived in the Liburnian region from the interior, from the central Balkans and the Danube basin, and the date of the finds from Dragišić is at earliest the 5th-4th centuries BC.
Keywords: Dragišić hillfort; southern Liburnian territory; multiheaded pins; astragal belts